Explanatory theoretical Model for Parenting Styles, Attachment Styles and Differentiation of couples - azad gorbani; ahmad amani (Faṣlnāmah-i Farhang Mushavirah va Ravān/Darmānī, 2015)
parenting style can be a predictor of early maladaptive schemas and marital satisfaction. Understanding variables that effect of parenting style is very important. The aim of this present study is to explanatory theoretical model to parenting style, attachment style and differentiation of couples. The research was a descriptive-correlational study. The population consisted of all teachers have a child and their spouses who were teaching in the academic in Kamyaran, Iran in 2014. The sample consisted of 500 parents (250 couples) who were selected by simple sampling method and completed differentiation of self, attachment style, parenting style. The data from the questionnaires were analyzed using AMOS software. The Results indicate a positive and significant correlation between authoritative parenting with secure attachment style, Iposition and reactivity emotional, and between permissive parenting with anxiety attachment style. Also negative and significant correlation was observed between authoritative parenting with emotional cutoff. Also significant correlation between attachment components with differentiation of self. The results indicate that levels of differentiation and attachment style can be a predictor of parenting style. Modification these two variables we can develop of authoritative parenting in parent.